(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe clinical features, determine the proportion of etiologies causing persistent hematospermia diagnosed by transurethral seminal vesiculoscopy, evaluate treatment outcomes, and report complications. Subjects and methods: Retrospective analysis of 13 male patients with persistent hematospermia (≥ 3 months) who underwent transurethral seminal vesiculoscopy at the Center of Andrology, Viet Duc University Hospital in 2025. Results: Median age was 34 (18-53) years. The leading pre-operative diagnoses were seminal vesiculitis/vasitis (46.2%), seminal vesicle/ejaculatory duct stones (30.8%), and varicose periprostatic veins (15.4%). Endoscopy helped clarify the etiology in cases without a definite pre-operative diagnosis. All patients received definitive intervention in the same session (stone fragmentation, irrigation, vein fulguration). Median operative time was 45 minutes, and median hospital stay was 5 days (range 3-9). No intraoperative or postoperative complications were recorded; 100% of patients had complete resolution of hematospermia. Conclusions: Transurethral seminal vesiculoscopy is a safe and effective method that allows accurate diagnosis and definitive treatment of persistent hematospermia in a single procedure.